Mourning dove period and annual survival in west‐central Missouri - John H. Schulz; Yuanyuan Bian; Xiaoming Gao; Tony W. Mong; Joshua J. Millspaugh (Wildlife Society Bulletin)
ABSTRACT We examined annual and period survival for mourning doves (Zenaida macroura) in Missouri, USA, using birds captured and marked on public land intensively managed for dove hunting. During 2005–2008, we radiomarked and monitored 713 birds to estimate period survival and banded 826 to estimate annual survival. For all ages, sexes, and years combined, spring‐summer survival prior to hunting season was 0.447 (95% CI = 0.378–0.517) and overall period survival during May–October, including hunting season, was 0.252 (95% CI = 0.200–0.303). Mean annual survival for after‐hatch‐year (AHY) doves was 0.214 (95% CI = 0.053–0.569) and 0.041 (95% CI = 0.002–0.506) for hatch‐year (HY) doves; recovery rates were 0.165 (95% CI = 0.105–0.249) for AHY and 0.179 (95% CI = 0.121–0.256) for HY doves. Our longer monitoring period allowed for a more robust picture of survival showing relatively low annual survival with few doves living beyond one year and significant mortality occurring prior to and during the hunting season. Differences in period survival each year likely reflect local differences in habitat influenced by weather and associated farming and management on the study area to attract feeding doves. Our results suggest locally intensive harvest management practices may be negatively affecting local populations and warrant continued monitoring to ensure long‐term population sustainability. © 2017 The Wildlife Society.